Determining the traffic safety management criteria in highway maintenance works from road users’ perspective / Suhaila Ali and Nur ‘Ain Ismail - Ali, Suhaila; Ismail, Nur ‘Ain (2012)
Road traffic injuries are a major public health problem and a leading cause of death, injury and disability around the world. Better plans, transparent process, and public support are some of the benefits that road managers can obtain by educating and involving the general public. This paper examines the perception of highway users towards the installation of the traffic safety equipment during road maintenance work and also determines the traffic safety management criteria in ensuring the traffic control signs and equipment in meeting the highway users’ needs. A survey has been conducted among the Malaysian road users from Ipoh to Kuala Lumpur. The researcher found that the overall perceptions of the respondents stated the installation of the traffic safety equipment during road maintenance work progress isbelow the average level. In term of traffic safety management criteria it must have criteria like all the traffic safety equipment should be brighter and visible from long distance, instruct drivers to follow a path away from where work is being done and concessionaire should be aware of their equipment in good condition and should do routine maintenance. From the analysis that has been carried out, the result shows that the management should improve the safety in work zones from the perception of respondents were analysed and discussed.